The crystal desert : summers in Antarctica - Campbell, David G. (Boston : Houghton Mifflin, 1992)
The Crystal Desert is not only the most eloquent book ever written about Antarctica but one of the best portraits of a place ever published. Most books about Antarctica have focused on the lifeless ice cap that smothers two-thirds of the continent and on the heroic marches toward the South Pole that have pitted humans against a frozen world. The Crystal Desert is about the other Antarctica, the "banana belt" of the Antarctic Peninsula. The interior of the peninsula is biological haiku: a few eloquent syllables of plants and animals. The tallest plant is a lichen ten centimeters high, the largest land animal a flightless midge two millimeters long. But the sea surrounding the peninsula brims with life like no other on Earth.
The Crystal Desert is a story of life's tenacity in this coldest and most alien of continents. It is a chronicle of events - of courtship, hatching, birth, growth, predation, and death - during the desperately short summer, when for three months the sun marches around the northern horizon and sets only briefly. It tells of penguins and seabirds and seals and whales, of the evolution of life in Antarctica, and of the evolution of the continent itself from the land mass known as Gondwana. It tells of the explorers who discovered Antarctica, of the whalers and sealers who despoiled it, and of the scientists working there today - especially at the Brazilian station, "Little Copacabana," where parties often last all night and Carnival runs for three days.
Prologue: Admiralty Bay -- 1. Seabirds and Wind -- 2. Memories of Gondwana -- 3. Life in a Footprint -- 4. Penguins and Hormones -- 5. The Galaxies and the Plankton -- 6. The Bottom of the Bottom of the World -- 7. The Worm, the Fish, and the Seal -- 8. Visions of Ice and Sky -- 9. The Indifferent Eye of God -- 10. The Tern and the Whale -- 11. The Passing of the Leviathans -- 12. The Tempest -- Appendix: Latin Names of Plants and Animals Mentioned in Text.
Includes bibliographical references (p. [282]-297).
Keywords: Campbell, David G. -- Journeys -- Antarctica; Natural history -- Antarctica; Summer -- Antarctica; Antarctica -- Description and travel